Water chemistry of nuclear reactor systems 6. (British Nuclear Energy Society, 1992)
Proceedings of sixth international conference held in Bournemouth on 12-15 October 1992.
Keywords: Nuclear reactors -- Congresses.; Water -- Congresses.; elektronické knihy; electronic books